2015
DOI: 10.1016/j.msea.2015.06.093
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics and intrinsic workability of IN718 superalloy

Abstract: a b s t r a c tThis study focuses on deformation characteristics of superalloy IN718 by formulation of a new flow stress model and detailed evaluation of intrinsic workability through the generation of three-dimensional (3D) processing maps with the support of optical microstructural observations. Based on thermomechanical simulation tests using a Gleeble-1500 machine, the flow stress model for superalloy IN718 was built and the flow stress throughout the entire deformation process was described by a peak stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 46 publications
(70 reference statements)
1
23
1
Order By: Relevance
“…Because there is no enough time for deformation heating to dissipate at high strain rate, the local temperature of deformed block sharply increases. Thus, flow localization occurs [26]. Besides, it can be found that there are a large amount of δ phases in grain interior and boundaries at the strain rate of 1 s -1 , as shown in Fig.…”
Section: Discussion Of Flow Softening Mechanismsmentioning
confidence: 83%
See 2 more Smart Citations
“…Because there is no enough time for deformation heating to dissipate at high strain rate, the local temperature of deformed block sharply increases. Thus, flow localization occurs [26]. Besides, it can be found that there are a large amount of δ phases in grain interior and boundaries at the strain rate of 1 s -1 , as shown in Fig.…”
Section: Discussion Of Flow Softening Mechanismsmentioning
confidence: 83%
“…Besides, it can be found that there are a large amount of δ phases in grain interior and boundaries at the strain rate of 1 s -1 , as shown in Fig. 10. δ phases, typical second-phase particles, can act as the geometric barrier to inhibit dislocations movement [26,52], which will result in the decreased flow softening degree. It is well known that the stresses for dislocations to overcome the further movement are mostly affected by the volume fraction and mean particle radius of second-phase particles.…”
Section: Discussion Of Flow Softening Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [36] established three-dimensional processing maps to assess the hot workability of Inconel 718 superalloy. Liu et al [37] discussed the effects of strain rate and deformation temperature upon hot workability of FGH4096 superalloy.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of forgings are extremely sensitive to the dynamic and interconnected variables, such as strain, strain rate and temperature [20]. Therefore, in recent years, the flow behaviors and microstructural evolution of IN718 have been studied experimentally by many researchers [21][22][23][24][25][26]. However, there have been few investigations on modeling and simulation of microstructure evolution for IN718 superalloy during hot working.…”
Section: Introductionmentioning
confidence: 99%